ANALISIS PENGARUH VARIABEL INTERN TERHADAP PENDAPATAN USAHA (Studi kasus Pada Pedagang Kaki Lima Makan dan Buah-buahan di Kota Malang) - Munir, Moh. (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2005)
The exsistence of informal sector in the cities is part of both macro and micro economic system. Implicity, the informal sector is needed and, indeed, its emergence conversely helps the formal sector. However, it is necessary to understand that some people resist its emergence and existence. Apart from the remark that the informal sector still needs some justification and approaches in order to minimize and to remove the resulted impacts, what is more important to know is that the incomes obtained from this sector are quite sufficient to ful fit the daily minimum basic needs. The objective of the study is to know the influence of the internal variables on the operational incomes of the street vendors. The internal variables consist of such independent variables as Personnel (X1), Finance/Capital (X2), Marketing (X3), and a dependent variable of Operational Incomes (Y). Therefore , the methodology concerning the objective pursued is as folloows: The data are colled using closed quistionnaires and purposive sampling. Its sample consists of 70 respondents. Then, the collected data are analyzed using a computer program of SPSS 12.00 n order to know their correlations and regressions. Based on the data nalyis, it is partially proven that all the internal variables have a positive correlation with the operational incomes, being seen from the correlational coefficient (r) of X1 =0.623 (P=0.000), X2 = 0.638 (P=0.000), X3 = 0.786 (P=0.000). Partially, all the internal variables have a significant influence on the operational incomes, being proven by the finding that the t table values of X1 = 4.959 (P=0.000), of X2 =3.972 (P=0.000) and of X3=7.017 >the t table value on DF (67:0.05) of 1.67. Simultaneously, the internal variables (X1,X2,X3) have a significant influence on the operational incomes, being proven by the finding that the F calc on DF (3:73:0.05) of 2.75. The contribution of each internal variable to the dependent variabel is that Operational Incomes : Personnel (X1) =32.37 %, Finance/Capital (X2) = 27,4% and Marketing (X3) = 50.7%. The internal varible having the most dominant influence on the operational incomes is Marketing (X3). Next, the amount of the influence can be simultaneously seen from the resulting R square of 0.774, meaning that the contribution of the internal variables simultaneously to the dependent variable is 77.4% where as the remaining 22.6% is influenced by other variables being not studied